The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1969
DOI: 10.1104/pp.44.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Production from Propanal

Abstract: Abstract. Tracer studies using a model system consisting of Cu2+ and ascorbate indicate that carbons 2 and 3 of propanal are converted to ethylene, and carbon 1 is converted to formic acid and CO2. A mechanism accounting for this reaction is described. In apple tissue, methionine but not propanal is readily incorporated into ethylene. It is therefore concluded that propanal is not a precursor of ethylene in this fruit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The rate of ethylene production increased linearly after this lag from 2.7 ± 0.3 nl g-' hr-' to the first maximum of 11.3 ± 1.8 nl g-' hr-' at 56 ± 2.1 min. The rate then decreased to a minimum of 4.9 ± 0.9 nl g-' hr-' at 90 ± 2.7 min, increased to a reduced second maximum of 8.4 ± 1.7 nl g-' hr-' at 1.31 ± 4.9 min, and then declined over a period of about 100 min to a production rate of about 4 cantly affect the timing or rate of wound ethylene synthesis. The characteristic pattern must therefore be the result of increased ethylene synthesis and not merely the result of facilitated diffusion of ethylene already present in the tissue through the newly exposed cut surfaces.…”
Section: Methodsmentioning
confidence: 92%
“…The rate of ethylene production increased linearly after this lag from 2.7 ± 0.3 nl g-' hr-' to the first maximum of 11.3 ± 1.8 nl g-' hr-' at 56 ± 2.1 min. The rate then decreased to a minimum of 4.9 ± 0.9 nl g-' hr-' at 90 ± 2.7 min, increased to a reduced second maximum of 8.4 ± 1.7 nl g-' hr-' at 1.31 ± 4.9 min, and then declined over a period of about 100 min to a production rate of about 4 cantly affect the timing or rate of wound ethylene synthesis. The characteristic pattern must therefore be the result of increased ethylene synthesis and not merely the result of facilitated diffusion of ethylene already present in the tissue through the newly exposed cut surfaces.…”
Section: Methodsmentioning
confidence: 92%
“…Stress-dependent release of methanol occurs due to modifications in cell wall pectins (Koerner et al, 2009; Li et al, 2017). Lipoxygenase (LOX) pathway volatiles are synthesized from linolenic and linoleic acids in a cascade of reactions (Baur and Yang, 1969; Gigot et al, 2010). Their synthesis is initiated by cell membrane breakdown followed by the release of free linoleic and linolenic acids and further sequential action of lipoxygenases, hydroperoxide lyases, alcohol dehydrogenases and acetyltransferases (UI Hassan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Samples of the gas phase of the reaction syringes or flasks were periodically analyzed for total and radioactive ethylene and carbon dioxide by gas chromatography and gas radiochromatography as previously described (1,2). In the oxygen-dependent experiments the concentrations of atmospheric nitrogen and oxygen were analyzed by gas chromatography utilizing a thermal conductivity detector and a series of two columns containing silica gel and molecular sieve.…”
Section: Methodsmentioning
confidence: 99%
“…Oxygen is essential for this endogenous production of ethylene (4, 10). Evidence from tracer studies in a number of plant tissues has shown that methionine serves as a precursor of ethylene in vivo (1,2,5,9,11, 18). The enzymic conversion of methionine analogues to ethylene catalyzed by peroxidase has been elucidated recently (7,12,13,15,17, 18); KMB,2 the methionine keto analogue, or methional (,B-methylthiopropionaldehyde) but not methionine, is the active substrate.…”
Section: Introductionmentioning
confidence: 99%